Frans Gregersen & Inge Lise Pedersen (eds.): The Copenhagen Study in Urban Sociolinguistics. Copenhagen 1991 (446 p). - Vigsø, Orla (HERMES - Journal of Language and Communication in Business, 1992)
Kjell Lars Berge & Ulla-Britt Kotsinas (eds.): Storstadsspråk och storstadskultur i Norden. Stockholm 1991 (234 p).